Value Added Tax and Economic Growth of Nigeria (2003-2022) - Oto, Theresa Ekpe; Wayas, Solomon (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study empirically examined the relationship between value added tax and economic growth of Nigeria. Time series data on Value Added Tax (VAT) revenue, Total (Federal Government) Revenue (TR), Total (Federal Government) Expenditure (TE) and Gross Domestic Product (GDP) from 2003 to 2022 sourced from the Central Bank of Nigeria (CBN) were analysed, using both simple regression analysis and descriptive statistical method. VAT was used as the independent variable while TR, TE and GDP were used as the dependent variables. Findings showed that VAT revenue accounts for a significant variation in TR, TE and GDP in Nigeria. A very significant and positive correlation also exist between VAT revenue and TE but that the contribution of VAT to TE cannot be directly traceable to any specific expenditure of government like health, education or payment of salaries. The study therefore recommends that government should use a certain percentage of VAT revenue to finance critical sectors of the economy like agriculture, power or health which have direct bearing on the citizens. This can be achieved by establishing a Value Added Tax Fund (VATFund) as is the case with Tertiary Education Trust Fund (TETFund) and other Trust Funds of government.